In situ polymerization of conducting polyaniline in bicontinuous cubic phase of lyotropic liquid crystal - Huang, N.M.; Khiew, P.S.; Radiman, S.; Kan, C.S.; Ahmad Md, S. (Elsevier, 2004)
The polymerization of conducting polyaniline (PANI) in lyotropic bicontinuous cubic phase consisted of poly(oxyethylene) 10 nonyl phenol ether (NP10), octane and water have been explored. The rheology measurements have been carried out in order to assess the phase behavior of the pure lyotropic mesophases, doped with reactant and after polymerization. It was found that the phase structure did not rupture upon polymerization as the complex modulus of the system after polymerization is maintained in the cubic phase region. The results of small-angle X-ray scattering (SAXS) also showed that the microstructure of the mesophase did not disrupt after the polymerization process and indicate the direct templating of polyaniline in the cubic lyotropic mesophase. The synthesized PANI particles have been characterized by energy filter transmission electron microscopy (EFTEM), UV-vis absorption and Fourier transform infrared (FTIR) spectroscopy. The spectroscopy studies revealed the presence of emeraldine salts in the polymer, and thus confirms that the prepared polyaniline is in conducting form. The microscopy results showed that the resulting polymers have spherical shape with mesopores structure, fairly monodispersed and in the size range of 100-300 nm, depending on the reactants concentration. Â© 2004 Elsevier B.V. All rights reserved.